A green and sustainable method for Capsicum volatilome investigation by means of headspace solid-phase microextraction combined with flow-modulated two-dimensional gas chromatography-mass spectrometry using hydrogen as carrier gas - Micaela Galletta; Mariosimone Zoccali; Donato Creti; Luigi Mondello; Peter Q. Tranchida (Green Analytical Chemistry, 2023)
The present research is focused on the development of a green and sustainable analytical method, based on the use of headspace solid-phase microextraction (HS SPME), and hydrogen as carrier gas, within the context of fast flow-modulation comprehensive two-dimensional gas chromatography-time-of-flight mass spectrometry (FM GC × GC-ToFMS), for the investigation of the volatile composition of Capsicum peppers. In such a respect, three different species were analysed: Annuum, Baccatum, and Chinense. Following HS SPME FM GC × GC-ToFMS analysis, a tile-based Fisher-ratio software was used to easily determine compounds that varied the most within the same variety of Capsicum samples. Particular emphasis was also devoted to the aroma profile of the thirty most sample-distinguishing compounds.